2010
DOI: 10.1007/s00709-010-0105-0
|View full text |Cite
|
Sign up to set email alerts
|

Do mitochondria in Dendrobium petal mesophyll cells form vacuole-like vesicles?

Abstract: Using transmission electron microscopy, we investigated the ultrastructure of mitochondria in petal mesophyll cells of the orchid Dendrobium cv. Lucky Duan, from the time of floral opening to visible petal senescence. Cells close to the vascular bundle contained many mitochondria, some of which showed internal degeneration. This inner mitochondrial breakdown was accompanied by an eightfold increase in mitochondrial volume. Small electron-dense granules (approximately 0.04 mum in diameter) at the periphery of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…An overview of the anatomy of the petal, using light microscopy, has been shown in a previous paper. 30 Briefly, the upper epidermis had large cells, bulging to the exterior. The lower epidermis had somewhat smaller cells.…”
Section: Cell Morphology and Cell Deathmentioning
confidence: 99%
“…An overview of the anatomy of the petal, using light microscopy, has been shown in a previous paper. 30 Briefly, the upper epidermis had large cells, bulging to the exterior. The lower epidermis had somewhat smaller cells.…”
Section: Cell Morphology and Cell Deathmentioning
confidence: 99%
“…No half-life data seem available for plant mitochondria. 112 No evidence has thus far been shown in plants for a role of macroautophagy in the degradation of mitochondria. Uptake of mitochondria into the vacuole by microautophagy, and subsequent degradation, has been shown in organisms other than plants (mainly yeasts), but also have not been reported in plants.…”
Section: Autophagy During Internal Degradation Of Chloroplasts and Otmentioning
confidence: 99%
“…The mitochondrial interior eventually becomes homogeneously electron-translucent. Kirasak et al 112 observed that small electron-dense granules (approximately 0.04 μm in diameter) remain visible at the periphery of the mitochondrial matrix during plant mitochondrion degeneration. Such granules are not found in any other organelle.…”
Section: Autophagy During Internal Degradation Of Chloroplasts and Otmentioning
confidence: 99%
“…In line, mitochondrion internal vesicle-like structures have been reported in mitochondria of patients with defective gene functions which cause pathological conditions, or during reconstruction of the matrix compartment after extensive osmotic swelling [279], [280] as well as in degenerating mitochondria in vascular bundle in petals of open Dendrobium cv. Lucky Duan flowers [281]. Therefore, one can speculate that some of the components identified in this study as mitochondrial-localized factors are involved in the formation of cristae as the induction of membrane curvature is comparable to vesicle formation [282].…”
Section: Discussionmentioning
confidence: 63%